Abordagem molecular na identificação de espécies candidatas de Hepatozoon sp.(Apicomplexa: Hepatozoidae) - PAIVA, Gleicierle Rodrigues (2022)
Hepatozoon spp. are more frequent intracellular protozoa in snakes. The objective of this study was the use of the molecular approach by the Automatic Barcode Gap Discovery method, to identify candidate species of the genus Hepatozoon, parasitizing the snakes: Clelia clelia and Drymarchoncorais. From the snakes were extracted blood samples and from them the DNA, from which a fragment of the 18S nuclear gene was amplified by means of the Polymerase Chair Reaction. Phylogenetic analysis indicated that Hepatozoon sp. of C. clelia and D. corals form distinct groups of the other species of the genus. The high posterior probability value (99%) indicates that Hepatozoon sp. of C. clelia and D. corals represent sister lines, although more data are needed to infer the phylogenetic relationships between them. The ABGD result identified the existence of 33 groups (prior maximal distance P = 0.001) for the initial partition, classifying Hepatozoon sp. C. clelia and D. corais as two distinct taxa, and may be considered as unconfirmed candidate species. Few studies deal with the relationship between Hepatozoon species, thus the morphological data traditionally used in the taxonomy of these groups makes it possible to compare them with other species of Hepatozoon, contributing to the description of the species diversity of the genus.